Tugas Dan Peran Guru Menurut Perspektif Pendidikan Islam - Yazidul Busthomi; Syamsul A’dlom (STIT Muhammadiyah Paciran Lamongan, 2022)
Being a teacher is a really noble job. He is responsible not only to make human children smart in the field of science, but also to have good morals in this life. A human child who at first does not understand anything, in front of a teacher is educated to understand life better and know the world. On his shoulders are the duties and responsibilities for the future sustainability of a generation that is smarter and more civilized. So noble is the job of a teacher as well as how heavy the task and responsibility of being a teacher is. This is why not everyone can be a successful teacher. Only certain people who have a love for children or students and are highly dedicated to the world of education are able to become teachers. This is the personality of a teacher who successfully teaches and educates in front of his students, the figure of a favorite teacher who is loved by his students. According to the perspective of Islamic education, in addition to serving as coaches and educators of students, teachers also have duties and roles as follows: 1.Corrector, 2.Inspirator, 3.Informer, 4.Organisator, 5.Motivator, 6.Initiator, 7. Facilitator, 8.Supervisor, 9.Demonstrator, 10.Class Manager, 11. Mediator, 12.Supervisor, 13.Evalator.